European Union Information Center in Balti: destination, opportunities, challenges (2011-2016) (Confluenţe Bibliologice, 2016)
The European Union Information Center was founded by the Delegation of the European Union in Scientiﬁc Library of Alecu Russo Balti State University, aiming to enhance the EU related ﬂow of information among academic community. In the article is described how the users are supported with information, knowledge and a forum for the expression of actively seeking thematic information on the implementation of European policies representatives, professional organizations, organized populations for interests, professionals and experts. Also, the author writes about promotion of Eubookshop website, variety of campaigns leading community policies and thus strengthen the traditional calendar of the European Communities symbolic dates – particularly the annual celebration of Europe Day.
Keywords: European Union Center; fundamental values; dissemination information; research